An experimental evaluation of convective heat transfer in multi-layered fibrous materials composed by different middle layer structures. (September 2021) - Xiong, Xiaoman; Venkataraman, Mohanapriya; Jašíková, Darina; Yang, Tao; Mishra, Rajesh; Militký, Jiří; Petrů, Michal
In this work, three types of multi-layered fibrous materials with different middle layer structures, including Struto nonwoven, Struto nonwoven with air pockets and Struto nonwoven with air pockets filled by aerogel particles, were prepared based on laser engraving technique and laminating method. A custom-built new device was fabricated to evaluate convective thermal behaviour of the multi-layered materials in cross flow. It was found that in cross flow the heat transfer coefficient of the multi-layered material with encapsulated aerogels is directly proportional to Reynolds number. There are considerable variances in heat transfer rates of the three structures at low airflow velocity (less than 10 m/s), but the values are very close at high airflow velocity. It is concluded that the air pockets and aerogels present in the multi-layered fibrous material have significant effect on convective thermal behaviour of the overall structure in cross flow. The finding is a new contribution to the field of aerogel-based fibrous materials as thermal insulators in building and industrial facilities.